Management and Performance Analysis of Strawberry Agribusiness Supply Chain (Case Study: Bantaeng Regency, South Sulawesi Province) - Muhtar, Imran; Rahmawati Saleh; Syahriati; Nurlina Kasim; Ahmad, Ilham (Indonesian Journal of Economic & Management Sciences, 2024)
Strengthening the production of quality local fruit is a must, given the unmet demand of the domestic market which is still dominated by imported fruit. This is an opportunity to optimize areas that are centers of superior fruit production, one of which is Bantaeng Regency with its superior fruit, strawberries. Problems in the development of strawberry agribusiness are related to the suboptimal performance of the supply chain. The research aims to map the supply chain, and supply chain management of strawberry agribusiness; identify the driving and inhibiting factors in the strawberry agribusiness supply chain; and to analyze the performance of the strawberry agribusiness supply chain in Bantaeng Regency. The research method used a qualitative approach with the support of quantitative data. Data collection was conducted through interviews, literature studies, and observations. Data processing used the help of POMWIN software ver. 3.0. The results showed that the strawberry supply chain in Bantaeng Regency is categorized as multi-channel, the supply chain management includes traditional and partnership patterns, the main driving factors are the potential for agro-tourism development and high demand, while the inhibiting factors include difficulties in obtaining quality seeds, and supply chain institutions